Food and nutrition intake recommendation during COVID-19 pandemic in the Philippines - Imelda Angeles- Agdeppa (Indonesian Nutrition Association, 2020)
The key to sustaining a good immune system is to consume nutrient-dense food at the right quantity to prevent nutritional deficiencies. Nourishing our body play a vital role to prevent, fight, and recover from infections